Analysis of Passenger Behavior from the Perspective of Public Administration (A Study of the Security Policy of Mutiara Sis Aljufri Palu Airport Related to the Prohibition of Carrying Explosives, Power Banks, Electronic Cigarettes, and Others) - Fery, Fery; Hanif, Abdul (Formosa Journal of Multidisciplinary Research, 2024)
This study aims to determine Passenger Behavior at Mutiara Sis Aljufri Airport, Palu, which examines it from a public administration perspective. Passenger behavior at Mutiara Sis Aljufri Airport, Palu, can be analyzed from a public administration perspective by considering how the interaction between passengers and government institutions and public services takes place. At Mutiara Sis Aljufri Airport, Palu, Aviation Security (Avsec) unit officers are officers at the forefront and are authorized to handle public services and are fully responsible for all matters relating to security at Mutiara Sis Aljufri Airport, Palu and can represent government agencies. This type of research is descriptive qualitative, data collection methods are observation studies, interviews, documentation, and data analysis techniques. The results of the study indicate that Avsec officers have carried out their duties according to Standard Operating Procedure (SOP). However, there are still uncooperative passengers, and there are still many passengers who do not or do not know the applicable regulations.